Synthesis and flow behaviour of carbon nanotubes nanofluids - Alias, Hajar; Ho, Phang Wei (Penerbit UTM Press, 2009)
The purpose of this study is to synthesize samples of Carbon Nanotubes (CNT) nanofluids and investigate its stability, particle structure and flow behaviour characteristics. Carbon nanotubes were dispersed in the base fluids of ethylene glycol (EG) and de-ionized water (DI-water) by the two-step method. Sodium dodecyl sulphate (SDS), a surfactant was used to assist the dispersion of nanoparticles in the fluid. The mixture was then homogenized using an ultrasonic bath. Observations showed that DI-water nanofluids were stable for more than 1 month, while diluted EG nanofluids lasted only 1 week. The SDS surfactant worked better in water-based liquids to reduce agglomeration in nanofluids. Scanning Electron Microscope (SEM) imaging showed the catalyst supports were still attached to the nanotubes, hence reducing its purity. Massive crystallization on the structure of CNT in EG nanofluids also supported the theory that SDS has reduced functionality in EG. For both base fluids, viscosity was shown to increase with particle concentration and decrease with increasing temperature between 30 °C and 60 °C. The magnitude of viscosity increments were underestimated by Einstein’s conventional viscosity model.